IMPLEMENTASI APLIKASI SHOPEE MENGGUNAKAN SISTEM COD-CEK DULU (STUDI PADA PELANGGAN SHOOPE DI TULUNGAGUNG ) - majid, muhamad maulana; bayu, bayu cahyoadi (STKIP PGRI Tulungagung, 2024)
Currently there are several marketplaces used by Indonesian society such as Shopee, Lazada, Tokopedia, Bukalapak and Blibli. There is some public interest in using several of these marketplaces because the first one is simple, there are many products available that people want, and there is a COD (Cash On Delivery) feature. In principle, the COD-Cek Dulu system is a payment method by paying in cash where consumers can check the goods first before payment is made when the goods arrive at their destination. The aim of this research is to determine the efforts made to increase shoppe customer satisfaction using the system. COD-Check first, the method used in this research is qualitative. The results of this research show that courier services play an important role in the efforts made to increase customer satisfaction in shoppe applications using the COD system.